Preparation method of tracer-activated carbon quantum dots and its application in reservoirs
Tracer-activated carbon quantum dots are prepared by reaction between urea and sodium citrate and modifier, which solves the problems of high cost of existing tracers and poor temperature resistance of surfactants, and achieves efficient monitoring and oil displacement in oil and gas fields dual performance, suitable for low permeability reservoirs.
Patent Information
- Application Number
- CN202410846099.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-27
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-06-27
AI Technical Summary
Existing tracers have problems such as high cost, high environmental hazards, complex analysis methods and expensive in oil and gas fields. It is difficult to effectively apply conventional oil and gas extraction technology to low permeability, ultra-low permeability, and dense reservoirs, and the resistance of surfactant Poor high temperature performance and limited scope of application.
Using a method of preparing tracer-activated carbon quantum dots, carbon quantum dots with fluorescence effects are prepared by reaction between urea and sodium citrate and a modifier, which can be used as tracer and oil repellent. Works effectively in high temperature and high mineralization environments and forms new nanofluids with surfactants through chemical grafting.
It realizes dual performances of low-cost, high temperature resistance, good salt resistance and oil dispersion, can efficiently monitor the water flow path and improve recovery rate in oil and gas fields, avoids the defects of surfactants, and has industrial synthesis and large-scale application. potential.
Smart Images

Figure CN118853156B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil and gas field exploitation, in particular to a method for preparing a tracer-activated carbon quantum and its application in a reservoir. Background Art
[0002] Most domestic oil fields have now entered the tertiary oil recovery stage, with water content in the high water content period and the ultra-high water content period. At the same time, the recovery rate is high, and it has entered the "double high" life period, and the dominant channels are developed. Understanding the strength and size of reservoir heterogeneity, the connectivity between injection wells and production wells, and mastering the flow field of injected water are of great significance for the regulation of dominant channels and improving the recovery rate. As an important carrier of inter-well tracer monitoring technology, tracers can enter the reservoir and carry fluid and geological information. Tracers are mainly divided into five categories: chemical, radioactive isotope, stable isotope, trace substance, and nano-quantum tracers. However, chemical tracers have the disadvantages of large injection volume and high cost; radioactive isotope tracers have great harm to the environment; stable isotope tracers have complex analysis methods and are expensive, and there are few stable isotopes that meet the conditions. Therefore, the existing tracers have different defects, and it is necessary to continuously study and improve tracer technology.
[0003] On the other hand, unconventional oil and gas resources are becoming more and more important in energy supply, so the exploration and development of unconventional oil and gas is of great significance. Low permeability, ultra-low permeability, and tight reservoirs have the characteristics of low porosity, low permeability, and large seepage resistance. Conventional oil and gas extraction technology is difficult to effectively apply to micro-nanoscale pores. Energy storage development is an effective way of oil recovery. Surfactants are commonly used energy storage and imbibition oil recovery agents. Their micro-nanoscale particle size can enter the pores of tight oil reservoirs. The mechanism of action is to improve the wettability of reservoir rocks and reduce the oil-water interfacial tension, thereby improving the recovery rate. However, the adsorption loss of surfactants in the reservoir is large, the high temperature resistance of surfactants is poor, and the interfacial activity is affected by factors such as temperature, mineralization, and water quality conditions, resulting in a limited scope of application of energy storage development. Therefore, it is still necessary to continue to explore and study new materials and technologies that can significantly improve the recovery rate of crude oil. Nanomaterials have a high relative surface area, small particle size, high fluidity in porous media, and can reduce interfacial tension and change rock wettability. Quantum dots are luminescent semiconductor nanostructures composed of a small number of quanta, usually with a size of several nanometers, and have optical properties, interface effects and quantum effects. Quantum dots, whose three-dimensional dimensions are all within the nanoscale range, have a unique size effect of nanostructured materials, which gives them unique properties such as large specific surface area, high activity, and wide band gap. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing carbon quantum dots having the dual properties of oil and gas reservoir tracing and oil displacement.
[0005] The preparation method of carbon quantum dots with dual performances of oil and gas reservoir tracing and oil displacement provided by the present invention comprises the following steps:
[0006] S1. Fully stir and mix urea and sodium citrate powder to form a mixture, heat the mixture to 60-80°C by water bath heating, then add the modifier preheated to 60-80°C to the mixture, and quickly stir until a white paste is formed. The modifier is selected from at least one of alkyl alcohol polyoxyethylene ether and polyethylene glycol. The molar ratio of urea to sodium citrate is (5-7):1. The mass of the modifier accounts for 15%-20% of the total mass of the reaction system in step S1.
[0007] S2. Heat the white paste of step S1 to 120°C-200°C and react for 1-4h to obtain a brown-black solid product.
[0008] S3. Grind the brown-black solid product, then add anhydrous ethanol and clean it with ultrasonic wave, and dry it to obtain a preliminarily purified brown-black powder.
[0009] S4. Dissolve the brown-black powder in ultrapure water and centrifuge. Take the supernatant from the centrifuge bottle and purify it by filtering it with ultrafiltration membranes with pore sizes of 0.45 microns and 0.22 microns in sequence. Then add the filtered solution into a dialysis bag with a cutoff molecular weight of 1000D, place it in ultrapure water for continuous dialysing for several hours, and finally dry the clear liquid in the dialysis bag to obtain a brown-black powder solid, which is the tracer-activated carbon quantum dots, and any one of its three-dimensional dimensions is within the range of 1-10nm.
[0010] Preferably, the carbon chain length of the alkyl alcohol polyoxyethylene ether fatty alcohol is 12-22, and the EO number is 3-35.
[0011] Preferably, in steps S3 and S4, the drying may be performed by freeze drying or heating drying, and the heating drying temperature is not higher than 80°C.
[0012] The carbon quantum dots prepared by the above method have a fluorescence effect, the best excitation wavelength is between 270-300nm, and the maximum fluorescence intensity is at the emission wavelength of 480-560nm.
[0013] The present invention also provides an application of the above-mentioned tracer-activated carbon quantum dots, which are used as tracers and oil displacement agents in oil and gas field exploitation. They are mainly suitable for water injection development of oil reservoirs, and the nanofluid is directly prepared with oil field injection water and then pumped into the formation.
[0014] The tracer-activated carbon quantum dots are used at an extremely low concentration, with an identification accuracy of ppm (parts per million). They can also be quickly prepared (within 5 minutes) in harsh environments (high temperature, high mineralization, pH, and complex water quality) and pumped into reservoirs for all-weather tracing of oil and gas reservoirs.
[0015] The tracer-activated carbon quantum dots can be used alone or in combination with other surfactants (such as sodium dodecylbenzene sulfonate, coconut oil diethanolamide, lauryl amide propyl hydroxysulfobetaine, etc.).
[0016] The average particle size of the tracer-activated carbon quantum dots is within 10nm, which can achieve full entry and spread of nanopores, nano-micropores, and micro-pore media. The main effects are: ① The tracer-activated carbon quantum dots reduce the oil-water tension by less than 1.0mN / m, ② Although the adsorption amount on the rock surface is extremely low (the cumulative recovery mass can reach more than 90%), ③ It can efficiently regulate the oil-wet / hydrophilic rock surface to a nearly super-water-wet state (the three-phase contact angle of the rock surface is 35°), ④ The tracer-activated carbon quantum dots are adsorbed at the oil-water interface, and can be used for in-situ emulsification and viscosity increase or in-situ viscosity reduction of crude oil according to different application scenarios, and the tracer-activated carbon quantum dots can achieve efficient oil displacement under the synergistic effects of ①+②+③+④.
[0017] Compared with the prior art, the present invention is beneficial in that:
[0018] (1) The present invention synthesizes tracer-activated carbon quantum dots in one step through an efficient, simple and green "solid phase bottom-up reaction method". The principle of this method is reliable, the raw materials are cheap and readily available, and it can be produced in large quantities at low cost. In terms of field application, the tracer-activated carbon quantum dot nanofluid can be directly prepared using formation injection water, without the need for an additional injection system, and can be dissolved by mechanical stirring, which has the potential for industrial synthesis and large-scale application.
[0019] (2) Compared with the existing method of using surfactants as energy storage and absorption oil recovery agents, the present invention uses surfactants and carbon quantum dots to form tracer-activated carbon quantum dots through chemical grafting. As the temperature rises, there is no turbidity point. The system solution is still in a clear and uniform state for a long time at high temperature. The tracer-activated carbon quantum dots show significant high temperature resistance and salt resistance, and still have good applicability in high temperature and high salt reservoirs. The technical defects of surfactants as energy storage and absorption oil recovery agents are avoided. In addition, compared with the existing method of using carbon quantum dots-surfactant compound systems as oil displacement agents, the present invention uses surfactants and carbon quantum dots to form a new tracer-activated carbon quantum dot through chemical reaction, and the amount of surfactant used is also small. In the carbon quantum dots and surfactant compound system, the surfactant exists independently and does not react chemically with the carbon quantum. Therefore, the surfactant still has the problem of poor temperature resistance and cannot be applied to high temperature reservoirs. The temperature resistance, salt resistance, and mineralization resistance are poor.
[0020] (3) Compared with single carbon quantum dots (pure carbon quantum dots not modified by modifiers), the tracer-activated carbon quantum dots of the present invention have better ability to reduce oil-water interfacial tension, improve rock surface wettability, and have better dispersion stability.
[0021] (4) The tracer-activated carbon quantum dot nanofluid can be used as a high-efficiency oil displacement agent to spontaneously enrich at the oil-water interface and emulsify the oil with low energy, and has the characteristics of high efficiency, economy, and environmental friendliness.
[0022] (5) The nanofluid of the tracer-activated carbon quantum dots of the present invention can not only accurately monitor the water flow path in the oil reservoir, providing a new reference for in-situ monitoring of reservoir communication, but also can be used as an oil displacement agent to achieve oil recovery by changing the properties of the water-rock-oil ternary system. Therefore, the tracer-activated carbon quantum dot nanoparticles of the present invention have the dual purpose of tracing and enhancing oil recovery.
[0023] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a diagram showing the effect of tracer-activated carbon quantum dot nanofluid on improving the wettability of oil-wet cores.
[0025] Figure 2 This is a diagram showing the effect of tracer-activated carbon quantum dot nanofluid on improving the wettability of hydrophilic cores.
[0026] Figure 3 This is a transmission electron microscopy image of tracer-activated carbon quantum dot nanofluid.
[0027] Figure 4 The fluorescence emission spectra of tracer-activated carbon quantum dot nanofluid at different excitation wavelengths.
[0028] Figure 5 This is a microscopic morphology of tracer-activated carbon quantum dot nanofluid assembled at the water-crude oil interface to form a water-in-oil emulsion.
[0029] Figure 6 This is the absorbance standard curve of the tracer-activated carbon quantum dot nanofluid.
[0030] Figure 7 This is a diagram showing the oil displacement effect of tracer-activated carbon quantum dot nanofluid. DETAILED DESCRIPTION
[0031] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0032] Example 1
[0033] Add 2.5g urea and 1.8g sodium citrate to the reaction vessel, grind them into fine powder particles, stir them thoroughly to mix them evenly, and heat them to 60°C in a water bath. Add 1.1g of the modifier cetearyl alcohol polyoxyethylene ether-20 preheated to 60°C to the mixed powder of urea and sodium citrate, and stir quickly to a white paste; heat the white paste to 180°C and keep the reaction at a constant temperature for 2h to obtain a preliminarily synthesized brown-black solid product; grind the brown-black solid product into fine powder particles mechanically and move it into a beaker, add anhydrous ethanol as a cleaning agent, and wash it repeatedly three times with ultrasonic waves, and then dry it at 70°C to obtain a preliminarily purified brown-black powder product; dissolve the preliminarily purified brown-black powder product in ultrapure water, and place the obtained dark brown solution in a centrifuge at a speed of 4000r / min for 20min to separate impurities. Take the supernatant from the centrifuge bottle and filter and purify it in turn using ultrafiltration membranes with pore sizes of 0.45 microns and 0.22 microns. The filtered solution was then added to a dialysis bag with a cutoff molecular weight of 1000D and placed in ultrapure water for continuous dialysis for several hours, during which the ultrapure water outside the dialysis bag was replaced several times until the outside of the dialysis bag was a colorless clear liquid. The clear liquid in the dialysis bag was then dried at 70°C to obtain a brown-black powdery solid, which was the tracer-activated carbon quantum dots.
[0034] Example 2
[0035] Add 2.3g urea and 2.0g sodium citrate to the reaction vessel, grind them into fine powder particles, stir them thoroughly to mix them evenly, and heat them to 70°C in a water bath. Add 1.1g of the modifier lauryl alcohol polyoxyethylene ether-10 preheated to 70°C to the mixed powder of urea and sodium citrate, and stir quickly to a white paste; heat the white paste to 200°C and keep the reaction at a constant temperature for 3h to obtain a preliminarily synthesized brown-black solid product; grind the brown-black solid product into fine powder particles mechanically and move it into a beaker, add anhydrous ethanol as a cleaning agent, and wash it repeatedly three times with ultrasonic waves, and then dry it at 70°C to obtain a preliminarily purified brown-black powder product; dissolve the preliminarily purified brown-black powder product in ultrapure water, and place the obtained dark brown solution in a centrifuge at a speed of 4000r / min for 20min to separate impurities. Take the supernatant from the centrifuge bottle and filter and purify it in turn using ultrafiltration membranes with pore sizes of 0.45 microns and 0.22 microns. The filtered solution was then added to a dialysis bag with a cutoff molecular weight of 1000D and placed in ultrapure water for continuous dialysis for several hours, during which the ultrapure water outside the dialysis bag was replaced several times until the outside of the dialysis bag was a colorless clear liquid. The clear liquid in the dialysis bag was then dried at 70°C to obtain a brown-black powdery solid, which was the tracer-activated carbon quantum dots.
[0036] Example 3
[0037] 2.6g urea and 2.0g sodium citrate were added to the reaction vessel, ground into fine powder particles, stirred thoroughly to make them evenly mixed, and heated to 80°C in a water bath. 1.1g of the modifier polyoxyethylene (10) tridecyl ether preheated to 80°C was added to the mixed powder of urea and sodium citrate, and stirred quickly to a white paste; the white paste was heated to 200°C and the reaction was continued at a constant temperature for 1.5h to obtain a preliminarily synthesized brown-black solid product; the brown-black solid product was mechanically ground into fine powder particles and transferred into a beaker, anhydrous ethanol was added as a cleaning agent, and ultrasonic washing was repeated three times, and then dried at 70°C to obtain a preliminarily purified brown-black powder product; the preliminarily purified brown-black powder product was dissolved in ultrapure water, and the obtained dark brown solution was placed in a centrifuge and centrifuged at a speed of 4000r / min for 20min to separate impurities. The supernatant in the centrifuge bottle was filtered and purified in turn using ultrafiltration membranes with pore sizes of 0.45 microns and 0.22 microns. The filtered solution was then added to a dialysis bag with a cutoff molecular weight of 1000D and placed in ultrapure water for continuous dialysis for several hours, during which the ultrapure water outside the dialysis bag was replaced several times until the outside of the dialysis bag was a colorless clear liquid. The clear liquid in the dialysis bag was then dried at 70°C to obtain a brown-black powdery solid, which was the tracer-activated carbon quantum dots.
[0038] Example 4
[0039] Add 3.0g urea and 2.0g sodium citrate to the reaction vessel, grind them into fine powder particles, stir them thoroughly to mix them evenly, and heat them to 70℃ in a water bath. Add 1.3g of modifier polyethylene glycol preheated to 70℃ to the mixed powder of urea and sodium citrate, and stir quickly to a white paste; heat the white paste to 150℃ and keep the reaction at a constant temperature for 1.5h to obtain a preliminarily synthesized brown-black solid product; grind the brown-black solid product into fine powder particles mechanically and move it into a beaker, add anhydrous ethanol as a cleaning agent, and wash it repeatedly three times with ultrasonic waves, and then dry it at 70℃ to obtain a preliminarily purified brown-black powder product; dissolve the preliminarily purified brown-black powder product in ultrapure water, and place the obtained dark brown solution in a centrifuge at a speed of 4000r / min for 20min to separate impurities. Take the supernatant from the centrifuge bottle and filter and purify it in turn using ultrafiltration membranes with pore sizes of 0.45 microns and 0.22 microns. The filtered solution was then added to a dialysis bag with a cutoff molecular weight of 1000D and placed in ultrapure water for continuous dialysis for several hours, during which the ultrapure water outside the dialysis bag was replaced several times until the outside of the dialysis bag was a colorless clear liquid. The clear liquid in the dialysis bag was then dried at 70°C to obtain a brown-black powdery solid, which was the tracer-activated carbon quantum dots.
[0040] Comparative Example 1
[0041] Based on the preparation method of Example 1, the modifier cetearyl alcohol polyoxyethylene ether-20 is removed to prepare pure carbon quantum dots. The specific preparation method is as follows:
[0042] Add 2.5g urea and 1.8g sodium citrate to the reaction vessel, grind them into fine powder particles, stir them thoroughly to mix them evenly, heat the mixture to 180℃ and keep the reaction at a constant temperature for 2h to obtain a crude product; grind the crude product into fine powder particles mechanically and move it into a beaker, add anhydrous ethanol as a cleaning agent, and wash it repeatedly three times with ultrasonic waves, and then dry it at 70℃ to obtain the first purified product; dissolve the product after preliminary purification in ultrapure water, and place the obtained dark brown solution in a centrifuge at a speed of 4000r / min for 20min to separate impurities. Take the supernatant of the centrifuge bottle and filter and purify it in turn using ultrafiltration membranes with pore sizes of 0.45 microns and 0.22 microns. Then add the filtered solution to a dialysis bag with a cutoff molecular weight of 1000D, place it in ultrapure water for continuous dialysis for several hours, and replace the ultrapure water outside the dialysis bag several times during the period until the outside of the dialysis bag is a colorless clear liquid. Then dry the clear liquid in the dialysis bag at 70℃ to finally obtain pure carbon quantum dots.
[0043] The performance test is as follows:
[0044] (1) Improve rock wettability testing
[0045] The tracer-activated carbon quantum dots prepared in Example 1 were dispersed in a 4 mg / L(Ca 2+ Mg 2+ The concentration is 0.15×10 4 mg / L) in mineralized water, stirred for 1 hour to prepare a tracer-activated carbon quantum dot nanofluid with a mass concentration of 0.15%, and two equal portions of the nanofluid were taken. Then the natural oil-wet core piece 1# and the natural hydrophilic core piece 2# (sandstone rock) were immersed in two portions of the tracer-activated carbon quantum dot nanofluid respectively. Under a sealed condition of 60°C, the tracer-activated carbon quantum dot nanofluid and the core piece were kept in contact, and the contact angle of the solid phase-water phase-crude oil of the two groups of core pieces was tested using a contact angle meter at different contact times. The effect of the tracer-activated carbon quantum dot nanofluid on improving the wettability of oil-wet and hydrophilic cores is as follows. Figure 1 and 2 shown.
[0046] The pure carbon quantum dots prepared in Comparative Example 1 were also tested according to the same wettability test method as above: the pure carbon quantum dots were dispersed in 6×10 4 mg / L(Ca 2+ Mg 2+ The concentration is 0.15×10 4 mg / L) in mineralized water, stirred for several minutes, prepared a carbon quantum dot nanofluid with a mass concentration of 0.15%, and divided it into two equal parts. Then, the natural oil-wet core piece 3# and the natural water-wet core piece 4# (sandstone rock) were immersed in two portions of carbon quantum dot nanofluids, respectively, and kept in contact with the core pieces at 60°C under a sealed condition, and the contact angle of the solid phase-water phase-crude oil of the two groups of core pieces was tested by a contact angle meter at different contact times. The test results are shown in Table 1.
[0047] Table 1. Test results of rock wettability by tracer-activated carbon quantum dot nanofluid and pure carbon quantum dot nanofluid
[0048]
[0049] Rocks with contact angles greater than 90° are oleophilic, and rocks with contact angles less than 90° are hydrophilic. As can be seen from Table 1, both the tracer-activated carbon quantum dot nanofluid and the pure carbon quantum dot nanofluid of Comparative Example 1 can change the oleophilic rock surface to a hydrophilic surface. However, compared with pure carbon quantum dots, the tracer-activated carbon quantum dot nanofluid prepared by the present invention has a more significant effect on improving the wettability of the rock surface. The oil-wet core surface undergoes wetting reversal earlier, and the final three-phase contact angle reaches 33.4°, which is strongly hydrophilic, and also further enhances the hydrophilicity of the hydrophilic rock surface.
[0050] (2) Temperature and salt resistance test
[0051] The mineralization degree is 6×10 4 mg / L(Ca 2+ Mg 2+ The concentration is 0.15×10 4 mg / L) of mineralized water, take five portions of the same amount of mineralized water, add the tracer-activated carbon quantum dots prepared in Example 2, the pure carbon quantum dots of Comparative Example 1, the surfactant lauryl alcohol polyoxyethylene ether-10, polyoxyethylene (10) tridecyl ether, and cetearyl alcohol polyoxyethylene ether-20, respectively, and prepare a fluid with a mass concentration of 0.3%, and age it at 60°C for 15 days. The experimental results are shown in Table 2. It can be seen that the three separate surfactants all have cloud points, and there is a relatively obvious coagulation phenomenon visible to the naked eye under the simulated formation water mineralization. Pure carbon quantum dot nanofluids also have the disadvantages of poor salt resistance, poor temperature resistance, and easy agglomeration. The tracer-activated carbon quantum dot nanofluid of the present invention can avoid surfactant flocculation and carbon quantum dot agglomeration.
[0052] Table 2. Evaluation of salt tolerance of tracer-activated carbon quantum dot nanofluids
[0053] System Type Precipitation phenomenon Tracer-Activated Carbon Quantum Dot Nanofluid No sedimentation Pure Carbon Quantum Dot Nanofluid There is condensation Lauryl Polyoxyethylene Ethyl Ether-10 There is condensation Polyoxyethylene (10) tridecyl ether There is condensation Cetearyl Ethoxylate-20 There is condensation
[0054] (3) Oil-water interfacial tension test
[0055] Prepare the mineralization degree of 1.0×10 4 mg / L(Ca 2+ Mg 2+ The concentration is 0.05×10 4 mg / L)、3.0×10 4 mg / L(Ca 2+ Mg 2+ The concentration is 0.15×10 4 mg / L)、5.0×10 4 mg / L(Ca 2+ Mg 2+ The concentration is 0.25×10 4 mg / L)、7×10 4 mg / L(Ca 2+ Mg 2+ The concentration is 0.35×10 4 mg / L)、10×10 4 mg / L(Ca 2+ Mg 2+ The concentration is 0.5×10 4 mg / L) of mineral water and stirred for 30 min.
[0056] Two equal portions of water of each mineralization degree were taken, and the tracer-activated carbon quantum dots in Example 3 and the pure carbon quantum dots in Comparative Example 1 were added to prepare nanofluids with a mass concentration of 0.3%, and ultrasonically dissolved and stirred for 5 minutes. The interfacial tension of the tracer-activated carbon quantum dot nanofluid and the pure carbon quantum dot nanofluid with degassed crude oil (density of 0.84 g / cm) at formation temperature (60°C) was measured using a spinning drop interfacial tension meter at 60°C and 6000 rpm. 3 , viscosity of 14.8 mPa·s) oil-water interfacial tension, the measurement time is 2 h, in order to obtain a stable interfacial tension value, the experimental results are shown in Table 3. It can be seen that the tracer-activated carbon quantum dot nanofluid has a range of 1.0 to 10×10 4 mg / L of mineralized water, the interfacial tension of oil and water is kept at 10 -1 -10 -2 The mN / m order of magnitude is significantly better than that of pure carbon quantum dot nanofluid, which indicates that the tracer-activated carbon quantum dot nanofluid of the present invention has good interfacial activity.
[0057] Table 3. Stable interfacial tension between tracer-activated carbon quantum dot nanofluid and crude oil
[0058]
[0059]
[0060] (4) Zeta potential test
[0061] Ultrapure water was used to prepare the tracer-activated carbon quantum dot nanofluid of Example 4 and the pure carbon quantum dot nanofluid of Comparative Example 1 with a mass concentration of 0.1%, and ultrasonic dissolution and stirring were performed for 5 minutes. 2 mL was taken from the tracer-activated carbon quantum dot nanofluid and the pure carbon quantum dot nanofluid for Zeta potential test. The average value of 5 measured values of Zeta potential was taken respectively, and the results are shown in Table 4. It can be seen that the surfaces of the tracer-activated carbon quantum dots and the pure carbon quantum dots are negatively charged, but the tracer-activated carbon quantum dot nanofluid has better dispersion stability than the pure carbon quantum dot nanofluid.
[0062] Table 4. Zeta potential of tracer-activated carbon quantum dot nanofluids
[0063]
[0064] (5) Tracer-Characterization of Activated Carbon Quantum Dots at Microscale
[0065] 15 mg of the tracer-activated carbon quantum dots of Example 1 were dispersed in 10 mL of ultrapure water and sealed and ultrasonicated for 5 min to obtain the tracer-activated carbon quantum dot nanofluid. The microscopic morphology of the tracer-activated carbon quantum dot nanofluid was observed by transmission electron microscopy (TEM). Figure 3 The TEM microscopic morphology shows that the tracer-activated carbon quantum dots are spherical to quasi-spherical black particles with a particle size between 3-10 nm and an average particle size of 7 nm.
[0066] (6) Fluorescence analysis of tracer-activated carbon quantum dot nanofluids
[0067] 10 mg of the tracer-activated carbon quantum dots of Example 2 were dispersed in 10 mL of ultrapure water to obtain a tracer-activated carbon quantum dot nanofluid. The fluorescence emission spectra at different excitation wavelengths were measured using a fluorescence spectrophotometer. The results are as follows: Figure 4 As shown. It can be seen from the fluorescence spectrum that the tracer-activated carbon quantum dots have good photoluminescence properties. The activated carbon dots have a strong fluorescence absorption band in the range of 200-280nm and a strong fluorescence emission band in the range of 500-550nm. The optimal excitation wavelength of the tracer-activated carbon quantum dots is 270nm, and the optimal emission wavelength is 525nm. It is worth noting that the activated carbon dots are excitation wavelength dependent. When the excitation wavelength gradually increases from 200 to 280nm, the fluorescence intensity of the emission spectrum first increases and then decreases. The fluorescence intensity reaches a maximum at 270nm, and as the excitation wavelength increases, the corresponding emission fluorescence intensity decreases. This shows that the tracer-activated carbon quantum dots can trace the injected medium very well.
[0068] (7) Evaluation of the emulsification performance of tracer-activated carbon quantum dot nanofluids
[0069] The tracer-activated carbon quantum dots prepared in Example 3 were dispersed in a 4 mg / L(Ca 2+ Mg 2+ The concentration is 0.35×10 4 mg / L) in mineralized water to prepare a tracer-activated carbon quantum dot nanofluid with a mass concentration of 0.3%, and stirred for 1h; then the tracer-activated carbon quantum dot nanofluid and degassed crude oil (60℃, shear rate 10s -1 The viscosity under the condition is 25.18mPa·s) and a group of mixed liquids with a total volume of 30mL are prepared according to the water-oil volume ratio of 7:3 (water content is 70%). After mixing evenly, place it in a 60℃ constant temperature water bath pot and seal it. Then stir it at a speed of 10000rpm for 3min in a 60℃ water bath, and observe the emulsification. Then, use a Leica microscope to observe the microscopic morphology of the particle size of the fully emulsified emulsion. The microscopic morphology of the water-in-oil emulsion formed is shown in the following figure: Figure 5 After stirring, the viscometer was used at 60°C and a shear rate of 10 s. -1The apparent viscosity of the emulsion was tested under the conditions of . The test results show that after the crude oil is emulsified, the viscosity of the emulsion is 4mPa·s, which is lower than the viscosity of the degassed crude oil (25.18mPa·s). The tracer-activated carbon quantum dots have achieved the effect of emulsification and viscosity reduction and reducing the adhesion work of crude oil.
[0070] (8) Study on the adsorption performance of tracer-activated carbon quantum dots
[0071] First, ultrapure water was used to prepare aqueous solutions of different concentrations (20, 40, 60, 80, 100 ppm) containing the tracer-activated carbon quantum dots prepared in Example 4 and placed in vials. The absorbance of the aqueous solutions of different concentrations was measured using an ultraviolet spectrophotometer, and a standard relationship curve between the system concentration and the absorbance was drawn as shown in FIG. Figure 6 As shown, the concentration of tracer-activated carbon quantum dots is linearly related to the absorbance. Use ultrapure water to prepare a tracer-activated carbon quantum dot system with a mass concentration of 0.1% and put it into a vial. Add 80-160 mesh rock particles into the vial at a solid-liquid ratio of 1:10, shake well and put it into a 60°C constant temperature oven, and shake the vial regularly to make the rock particles fully contact with the tracer-activated carbon quantum dot system. After 72 hours, take the supernatant of the solution, and centrifuge the supernatant for 20 minutes at a speed of 4000r / min. Take the supernatant again, and use an ultraviolet spectrophotometer to measure the absorbance of the liquid after centrifugation. Use the standard curve formula to calculate the concentration, which is the concentration after adsorption, and calculate the adsorption amount. The adsorption amount result is 1.25mg / g. The rock static adsorption experiment shows that the adsorption loss of tracer-activated carbon quantum dots on the surface of rock particles is small, and it can be used as a better oil displacement agent and can meet the on-site construction.
[0072] (9) Tracer-activated carbon quantum dot nanofluids improve oil recovery performance
[0073] The mineralization degree is 5.0×10 4 mg / L(Ca 2+ Mg 2+ The concentration is 0.25×10 4 mg / L) of mineralized water, add the tracer-activated carbon quantum dots synthesized in Example 1, ultrasonicate and stir for 5 minutes to prepare a tracer-activated carbon quantum dot nanofluid with a mass concentration of 0.3%. Artificial sandstone core (d = 25.32 mm, L = 53.92 mm, gas permeability 4.52 mD, porosity 13.36%), experimental temperature 60 ° C, crude oil viscosity 14.5 mPa·s, original oil saturation about 53.2%.
[0074] In the water flooding stage (displacement rate 0.05mL / min), affected by the unfavorable water-oil mobility ratio, the water flooding degree was low, and the recovery rate was 34.21% at a water content of 98%. After the tracer-activated carbon quantum dot nanofluid was injected, the injection pressure increased and oil came out at the outlet. The tracer-activated carbon quantum dot nanofluid self-assembles at the oil-water interface, and improves the oil displacement efficiency by expanding the swept volume, improving the wettability of the core, reducing the oil-water interfacial tension, forming a water-in-oil emulsion under shear induction, and improving the oil-water mobility ratio to stabilize the displacement front. The results of the core physical simulation experiment show that the displacement of 0.5 times the pore volume of the tracer-activated carbon quantum dot nanofluid and the subsequent water flooding increased the crude oil recovery by 21.05%, and the cumulative recovery was 55.26%. The displacement effect is shown in Figure 7 The tracer-activated carbon quantum dot nanofluid exhibits the advantages of low concentration and high performance, and has a significant effect in improving oil recovery.
[0075] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for preparing tracer-activated carbon quantum dots, characterized in that: The following steps are involved: S1. Fully stir and mix urea and sodium citrate powder to form a mixture, heat the mixture to 60-80° C. by water bath heating, then add a modifier preheated to 60-80° C. to the mixture, and quickly stir until a white paste is formed; the modifier is selected from at least one of alkyl alcohol polyoxyethylene ether and polyethylene glycol; the alkyl alcohol polyoxyethylene ether fatty alcohol has a carbon chain length of 12-22 and an EO number of 3-35; S2, heating the white paste in step S1 to 120°C-200°C for 1-4h to obtain a brown-black solid product; S3, grinding the brown-black solid product, then adding anhydrous ethanol and ultrasonic cleaning, and drying to obtain a preliminarily purified brown-black powder; S4. Dissolve the brown-black powder in ultrapure water and centrifuge. Take the supernatant from the centrifuge bottle and filter and purify it using ultrafiltration membranes with pore sizes of 0.45 microns and 0.22 microns in sequence. Then add the filtered solution into a dialysis bag with a cutoff molecular weight of 1000D, place it in ultrapure water and dialyze it continuously for several hours. Finally, dry the clear liquid in the dialysis bag to obtain a brown-black powder solid, which is the tracer-activated carbon quantum dots, and any one of its three-dimensional dimensions is within the range of 1-10nm.
2. The method for preparing tracer-activated carbon quantum dots according to claim 1, characterized in that: In step S1, the molar ratio of urea to sodium citrate is (5-7):
1.
3. The method for preparing tracer-activated carbon quantum dots according to claim 2, characterized in that: The amount of the modifier used accounts for 15%-20% of the total mass of the reaction system in step S1.
4. The method for preparing tracer-activated carbon quantum dots according to claim 1, characterized in that: In steps S3 and S4, the drying operation adopts freeze drying or heating drying, and the heating drying temperature is not higher than 80°C.
5. An application of tracer-activated carbon quantum dots prepared by the preparation method according to any one of claims 1 to 4, characterized in that: It is also used as a tracer and oil displacement agent in oil and gas field exploitation.
6. The use of tracer-activated carbon quantum dots as claimed in claim 5, characterized in that: Used in water injection development of oil reservoirs, the nanofluid is directly prepared with oil field injection water and then pumped into the formation.
7. The use of tracer-activated carbon quantum dots as claimed in claim 5, characterized in that: Nanofluids can be quickly prepared within 5 minutes using either high-mineralization water or high-pH water, and then pumped into the reservoir for all-weather tracing of oil and gas reservoirs.
